Where Rivers Meet the Sea : The Political Ecology of Water - Kane, Stephanie C. (Book collections on Project MUSE., 2012)
Where fresh water appears to be abundant and generally accessible, chronic pollution may be relatively ignored as a public issue. Yet there are those whose lives, livelihoods, and traditions are touched directly by the destructive albeit essential relationship between humans and water. In her passionate and persuasively argued Where Rivers Meet the Sea, Stephanie Kane compares two cities and nations-Salvador, Brazil and Buenos Aires, Argentina-as she tells the stories of those who organize in the streets, petition the courts, and challenge their governments to implement and enforce existing la.